The Problem of the Acceleration of Electrons of the Outer Radiation Belt and Magnetospheric Substorms Space Science - Stepanova, M (Springer Berlin, 2015)
Predicting of the location of the maximum in high-energy electron fluxes filling a new radiation belt is an endeavor being carried out by physicists studying the magnetosphere. We analyzed the data from the Defense Meteorological Satellite Program (DMSP) satellites and ground-based magnetometers obtained during geomagnetic storm on 8-9 October 2012. The minimum value of the disturbance storm time (Dst) was -111 nT, and the maximum in high-energy electron fluxes that appeared during the recovery phase was observed at L∈=∈4∈Re. At the same time, we analyzed the motion of the auroral oval toward lower latitudes and related substorm activity using the data of the low-orbiting DMSP satellites and the IMAGE magnetic meridian network. It was found from the DMSP satellites measurements that the maximum of the energy density of precipitating ions, the maximum of the plasma pressure, and the most equatorial part of the westward auroral electrojet are all located at the 60° geomagnetic latitude. This value corresponds to L∈=∈4∈Re, i.e.; it coincides with the location of the maximum in high-energy electron fluxes. This L-value also agrees with the predictions of the Tverskaya relation between the minimum in Dst variation and the location of the maximum of the energetic electron fluxes, filling a new radiation belt. The obtained results show that the location of this maximum could be predicted solely from the data of the auroral particle precipitations and/or ground-based magnetic observations. © 2015 Antonova and Stepanova.
Keywords: Magnetospheric storm and substorm; Outer radiation belt; Auroral oval